Original paperAnalysis of the impact of selected socio-demographic factors on quality of life of asthma patients - Szynkiewicz, Ewa; Filanowicz, Małgorzata; Graczyk, Małgorzata; Cegła, Bernadeta; Jabłońska, Renata; Napiórkowska-Baran, Katarzyna; Bartuzi, Zbigniew (Advances in Dermatology and Allergology/Postępy Dermatologii i Alergologii, 2013)
Aim: To evaluate the influence of selected socio-demographic factors on quality of life of patients with different degrees of asthma severity. Material and methods: The study was conducted in 2009–2010 in the Clinic of Allergology, Clinical Immunology and Internal Diseases in Dr J. Biziel University Hospital No. 2 in Bydgoszcz. Patients were divided into a tested group (126) and a control group (86). The criterion for the division was the degree of asthma control according to GINA 2006. The following tools were used: the author’s questionnaire containing questions about socio-demographic and clinical data, and the WHOQOL-100. Results: In the tested group, a statistically significant correlation was observed between quality of life and age (p < 0.002 for the entire population), education (p < 0.05 in the group with controlled asthma, p = 0.0005 for the entire population), professional activity (p < 0.003 in the group with partially controlled asthma, p < 0.05 with uncontrolled asthma and p < 0.0001 in the entire population), marital status (p = 0.025 for the entire population) and financial situation (p < 0.0001; p < 0.0002; p < 0.009 in all groups; p < 0.0001 in the entire population). There was no significant difference between quality of life, and sex and the place of residence of the respondents. Conclusions: Age, education, professional activity, marital status and financial situation affect the assessment of quality of life in patients with asthma. Socio-demographic factors such as sex and the place of residence do not influence the assessment of quality of life in patients with asthma.